PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL, DAN DISIPLIN TERHADAP KINERJA PERAWAT PADA RS PMC PEKANBARU - Yenti, Nofri; Amsal, Chairul; ', Machasin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The population and samples in this study is all employee about 82 people. The data recourses used were primary and secondary data. The data accumulation technique used were taken by doing interview and questionnaire. The method of analysis used were the method of quantitative descritive and multiple regression analysis (simultaneously and partially analysis) with the help of SPSS 19 version. Based on the results of multiple linear regression analysis, simultaneously (together) three variables: emotional intelligence (X1) intelligence (X2) and discipline (X3) significantly affect the performance of nurses (Y). The degree of influence of each independent variable on the dependent variable can be determined by performing a partial test, the results obtained are: emotional intelligence variables (X1) significantly affects the performance of nurses variable (Y), intellectual variables (X2) significantly affects the performance of nurses variable (Y) and the discipline variable (X3) significantly affects the performance of nurses variable (Y).To the authors recommend that hospitals consider the factors that affect the performance of nurses as hospitals and nurses are working partners who need each other for survival of the hospitalKeywords: Emotional Intelligence, Intellectual Intelligence, Discipline and Performance nurse.